ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2010-2013) (Students' Journal of Accounting and Banking, 2015)
The aim of this research for analyzing factors that affecting effective tax rate on the financial statements of a manufacturing company in the Stock Exchange during 2010-2013 by using the concept of agency theory. The population used in this study, that the companies listed in Indonesia Stock Exchange during the years 2010-2013 in a row, the sample is determined, which is a manufacturing company that publishes financial statements 2010-2013 year in a row, manufacturing companies have independent commissioner 2010-2013 year in a row, the company manufactures using rupiah years 2010-2013 respectively. In hypothesis testing methods, ie using linear analysis. The result of the research using regression proves that size (the size of the company) gives a significant and negative impact on the effective tax rate, Profitability gives no significant but negative impact on the effective tax rate, independent directors had a significant and negative impact on the effective tax rate and leverage gives positive but not a significant effect on effective tax rate. This research supports the agency theory about how a company determines an effective tax rate based on the existing regulation with a fixed benefit even though the corporate tax is cut to pay for current and deferred tax.Keywords: Size, Profitability, Independent Directors, Leverage, Effective Tax Rate